A cultural history of objects in the modern age - Wilkie, Laurie A. 1968-; Chenoweth, John M. (The cultural history of objects, 2022)
Cover -- Contents -- List of Illustrations -- Series Preface -- Introduction Laurie A. Wilkie and John M. Chenoweth -- 1 Objecthood Christopher Witmore -- 2 Technology Steven A. Walton and Timothy J. Scarlett -- 3 Economic Objects Paul Graves-Brown -- 4 Everyday Objects Stacey L. Camp -- 5 Art Susanne Küchler and Timothy Carroll -- 6 Architecture Paul R. Mullins -- 7 Bodily Objects Laurie A. Wilkie, Katrina C. L. Eichner, Kelly Fong, David G. Hyde, Alyssa Scott, and Annelise Morris -- 8 Object Worlds Alfredo González-Ruibal -- Notes -- Bibliography -- Notes on Contributors -- Index.